Biological Behavioral Alterations of the Post-neural Differentiated Dental Pulp Stem Cells Through an in situ Microenvironment - Luo, Lihua; Wang, Xiaoyan; Zhang, Yanni; Wu, Yuwei; Hu, Fengting; Xing, Zhenjie; Wang, Lei; Xiao, Jian; Guastaldi, Fernando; He, Yan; Ye, Qingsong (Frontiers in Cell and Developmental Biology, 2020)
Transplantation of undifferentiated dental pulp stem cells (DPSCs) may suffer from tumorigenesis. Neuronal differentiated DPSCs (d-DPSCs) have emerged as an ideal source to treat central nervous system (CNS) disorders. Moreover, different components of culture medium functioned on the characteristics of d-DPSCs in vitro. In this study, d-DPSCs were cultured in three types of medium: Neurobasal®-A medium supplemented with 2% B27 (the 2% B27 NM group), Neurobasal®-A medium supplemented with 2% B27 and 5% FBS (the 2% B27+5% FBS NM group), and α-MEM containing 10% FBS (the 10% FBS α-MEM group). We found that d-DPSCs in the 2% B27+5% FBS NM group had lower proliferation and reduced expression of transient receptor potential canonical 1 (TRPC1) and CD146, whereas up-regulated Nestin and microtubule-associated protein-2 (MAP-2). Notably, d-DPSCs in the 10% FBS α-MEM group possessed high proliferative capacity, decreased expression of neuron-like markers and partially restored stemness. It was demonstrated that d-DPSCs cultured in the 2% B27+5% FBS NM could maintain their neuron-like characteristics. Besides, d-DPSCs cultivated in the 10% FBS α-MEM could partially recover their stem cells properties, indicating that neural differentiation of DPSCs was reversible and could open novel avenues for exploring the pluripotency of DPSCs.